Bridging prion biology and Alzheimer’s disease: from pathogenic seeds to precision therapeutics - Wang, Wenjin; Feng, Zhanhui; Shu, Lingfeng; Hu, Yongmei; Chen, Yuting; Zhang, Baihui; Huang, Hua (Frontiers in Molecular Neuroscience, 2025)
Alzheimer’s disease (AD) is characterized by the pathological aggregation of amyloid-beta (Aβ) and tau proteins, which display self-templating propagation reminiscent of the prion protein (PrPSc). Despite these similarities, distinct structural heterogeneities and host interaction mechanisms offer unique avenues for disease-modifying therapies. This review comprehensively synthesizes recent advancements addressing: (1) the conformational commonalities and strain-specificities shared between Aβ/tau and PrPSc; (2) the spatiotemporal dissemination patterns of pathogenic seeds within neural networks; and (3) the development of biomarkers and therapeutic strategies rooted in prion theory. By integrating insights from prion biology with AD pathogenesis, we propose a comprehensive “conformation-propagation-microenvironment” framework for precision intervention, thereby offering a novel paradigm to surmount current therapeutic limitations.